Commentary on special issue: Syntax and verbal short term memory. Issue 4 (August 2020) - Riches, Nick
Short term memory (STM) and working memory (WM) performance consistently predict language abilities in children with developmental language disorders. However, causality is not fully established. Moreover, evidence from the fine-grained analysis of STM/WM tasks and comprehension of complex sentences, suggests that long term memory (LTM) representations play an important role. Critical assessment of the articles in the special edition focuses on Zebib et al. and Stanford and Delage. Zebib et al. find that sentence repetition by bilingual language-impaired children more strongly reflects WM than overall linguistic ability. This suggests a dependence on WM when linguistic representations are impoverished. However, the process of ranking predictors is problematic. Stanford and Delage find that STM/WM difficulties affect the processing of complex sentences by individuals with Specific Learning Disabilities. Yet, LTM-based explanations focusing on input frequency may also explain this phenomenon. To make progress we need a combination of experimental studies and large-scale longitudinal studies.